Case Report: Analysis of short-term clinical efficacy of trilaciclib in patients with advanced lung neuroendocrine carcinoma undergoing chemotherapy - Zeng, Yan; Lin, Nan (Frontiers in Oncology, 2025)
Lung neuroendocrine carcinoma is a rare heterogeneous tumor with the characteristics of high invasiveness, low incidence, and poor survival prognosis. Currently, there is a lack of effective treatment measures, and treatment strategies are mostly extrapolated from small cell lung cancer and non-small cell lung cancer protocols. Studies have shown that more than 55% of patients with extensive-stage small cell lung cancer experience grade 3 or higher myelosuppression after receiving platinum/etoposide-containing chemotherapy, including neutropenia, anemia, and thrombocytopenia. myelosuppression can also increase the risks of infection, bleeding, etc. Severe myelosuppression may delay treatment, reduce dosage, stop medication, and cause other risks that affect tumor prognosis. The results of the study showed that the incidence of grade 3 or higher myelosuppression in patients using trilaciclib (a cyclin-dependent kinase 4/6 [CDK4/6] inhibitor) when receiving platinum-based chemotherapy was significantly lower than that in patients who did not use this drug. In addition, the use of trilaciclib did not affect the anti-tumor effects of chemotherapy and immunotherapy agents during the chemotherapy cycle. This study aimed to explore the effect of trilaciclib on chemotherapy-induced myelosuppression (CIM) in patients with pulmonary neuroendocrine carcinoma undergoing chemotherapy, and to provide a reference for improving patients’ treatment tolerance and quality of life in clinical practice.